2019
DOI: 10.1177/0269215519852130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the responsiveness of the Utrecht Scale for Evaluation of Rehabilitation (USER) and the Barthel Index in stroke patients

Abstract: Objective: To compare the responsiveness of the Utrecht Scale for Evaluation of Rehabilitation (USER) to the responsiveness of the Barthel Index in stroke patients in an inpatient rehabilitation facility. Design: Observational study. Setting: Inpatient rehabilitation facility. Subjects: Consecutive stroke patients admitted for clinical rehabilitation. Interventions: Not applicable. Main measures: The USER and the Barthel Index were administered by a nurse at admission and discharge. The Effect Size and Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the focus should be on early neurorehabilitation for all stroke patients and especially for women. Post-stroke loss to follow-up was reported from the national Austrian Acute Stroke Unit Registry as well as from Sweden with women being more likely to display ADL dependency, independent of stroke severity (Ullberg et al, 2016a;Willers et al, 2018). In another study, 22% of patients reported unmet rehabilitation needs at 12 months (Ullberg et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the focus should be on early neurorehabilitation for all stroke patients and especially for women. Post-stroke loss to follow-up was reported from the national Austrian Acute Stroke Unit Registry as well as from Sweden with women being more likely to display ADL dependency, independent of stroke severity (Ullberg et al, 2016a;Willers et al, 2018). In another study, 22% of patients reported unmet rehabilitation needs at 12 months (Ullberg et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Patients more often suffered from post-stroke depression and insufficient pain management; female sex was a predictor of worse outcomes (Ullberg et al, 2016b). Application and timing of rehabilitation depends on the health care providers as well as on the ability and willingness of the patients, and probably, on psychosocial determinants (Ullberg et al, 2016a). However, post-stroke ADL scores were consistently worse in women even after adjustment for psychosocial factors like education, medical insurance, and marital status (Lisabeth et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADL functioning will be assessed with the Barthel Index, Utrecht Scale for the Evaluation of Rehabilitation (USER) or Functional Independence Measure (FIM), depending on use in the participating country. The USER (16) and FIM (17,18) will be converted afterwards to the Barthel Index using standardised approaches.…”
Section: Primary Outcomementioning
confidence: 99%
“…The World Health Organization defines stroke as “the rapid onset of clinical symptoms of focal or global brain dysfunction, which lasts longer than 24 h or leads to death, with no other apparent cause than a vascular injury” [ 1 ]. The number of stroke patients around the world has increased considerably in recent decades [ 2 ], especially since the global pandemic started, where stroke arose as a complication of COVID-19, although up to now, its incidence remains unknown [ 3 , 4 ]. Clinical manifestations are wide and varied, including motor, sensory, perception and cognitive disturbances; urinary and faecal incontinence; swallowing and visual problems; and pain, communication and behavioural alterations [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%